Pengaruh Model Pembelajaran Ditempat Latihan Pramuka Usia Prasiaga Terhadap Perkembangan Sosial Anak Usia 5-6 Tahun (Penelitian Pre-Eksperimen di RA Al-Hidayah Pondoksalam Kabupaten Purwakarta) - Wini Wapiroh; Miftachul Jannah; Annisa Purwani (CV Putra Publisher, 2024)
This study aims to examine the influence of the learning model in the pre-scout training setting on the social development of children aged 5-6 years at RA Al-Hidayah, Kabupaten Purwakarta. The subjects of the study comprised 22 children in group B. The research method employed a one-group pre-test post-test design with four pre-scout activities. Data were collected through pre-tests, post-tests, and interviews with educators. The research variables included pre-scout learning (x) and social development (y). The pre-test results showed an average score of 105.50, indicating a lack of discipline, responsibility, and self-confidence among the children. After the intervention, the average post-test score significantly increased to 160.91. Analysis using the paired sample t-test revealed a significant difference, with a t-test value of -30.820, df = 22, standard deviation = 8.433, and sig. (2-tailed) = 0.000, indicating a significant improvement between the pre-test and post-test results. Based on the research findings, it can be concluded that pre-scout learning has a significant impact on the social development of children aged 5-6 years at RA Al-Hidayah. Pre-scout learning has proven effective in integrally enhancing children’s habits, discipline, self-confidence, responsibility, cooperation, knowledge, attitude, and skills in daily life. These findings support pre-scout guidelines that emphasize the importance of activity-based education outside the classroom for the social development of early childhood. Therefore, the integration of pre-scout learning methods into the early childhood education curriculum and the improvement of teacher competence in managing pre-scout activities are highly recommended.